Three-dimensional paleohistology of the scale and median fin spine of Lophosteus superbus (Pander 1856) - Anna Jerve; Qingming Qu; Sophie Sanchez; Henning Blom; Per Erik Ahlberg (PeerJ, 2016)
Lophosteus superbus is one of only a handful of probable stem-group osteichthyans known from the fossil record. First collected and described in the late 19th century from the upper Silurian Saaremaa Cliff locality in Estonia, it is known from a wealth of disarticulated scales, fin spines, and bone fragments. In this study we provide the first description of the morphology and paleohistology of a fin spine and scale from Lophosteus using virtual thin sections and 3D reconstructions that were segmented using phase-contrast synchrotron X-ray microtomography. These data reveal that both structures have fully or partially buried odontodes, which retain fine morphological details in older generations, including sharp nodes and serrated ridgelets. The vascular architecture of the fin spine tip, which is composed of several layers of longitudinally directed bone vascular canals, is much more complex compared to the bulbous horizontal canals within the scale, but they both have distinctive networks of ascending canals within each individual odontode. Other histological characteristics that can be observed from the data are cell spaces and Sharpey’s fibers that, when combined with the vascularization, could help to provide insights into the growth of the structure. The 3D data of the scales from Lophosteus superbus is similar to comparable data from other fossil osteichthyans, and the morphology of the reconstructed buried odontodes from this species is identical to scale material of Lophosteus ohesaarensis, casting doubt on the validity of that species. The 3D data presented in this paper is the first for fossil fin spines and so comparable data is not yet available. However, the overall morphology and histology seems to be similar to the structure of placoderm dermal plates. The 3D datasets presented here provide show that microtomography is a powerful tool for investigating the three-dimensional microstructure of fossils, which is difficult to study using traditional histological methods. These results also increase the utility of fin spines and scales suggest that these data are a potentially rich source of morphological data that could be used for studying questions relating to early vertebrate growth and evolution.